Leopold Blaustein vs. Edmund Husserl - Gilicka, Magdalena (Phainomena (Ljubljana), 2025)
The article presents Husserl’s conception of imaginative variation and intentional consciousness while considering the philosophy of Leopold Blaustein. The Polish philosopher’s critical analyses regarding the validity and feasibility of the operation of variation as well as Husserl’s account of consciousness, on the one hand, reveal shortcomings in Blaustein’s philosophical reflections, and, on the other hand, nonetheless lead us to points of convergence between their concepts. What emerges in Blaustein’s thought is, alongside his philosophical maturity and independent scholarly approach, an interesting application of Husserlian categories.
Keywords: consciousness; constitution; imaginative variation; imaginativna variacija; intencionalnost; intentionality; konstitucija; perception; zavest; zaznavanje